Kim byli „Wołod´ko” i „Biłyj”? O rzekomym istnieniu UPA na terenie województwa wrocławskiego w latach 1947–1951 - Syrnyk, Jarosław (Pamięć i Sprawiedliwość, 2007)
Both in quasi-historian literature and in serious historiography one can find statements that in Poland after 1948 structures of Organisation of Ukrainian Nationalists (OUN) and Ukrainian Insurgent Army (UPA) existed. To support this thesis authors bring information about activities of so called “Zenon’s” net and of “partisan groups” in provinces of Olsztyn and Włocław.In “Zenon” case, despite the complexity of the problem, in the light of researches led by i.e. I. Hałagida, it is clear, that that was a provocative structure, organised and controlled by Ministry of Public Security (MBP). As far as the case of partisan groups in Olsztyn province, is concerned, their activities did not go beyond 1948. In the current article the author tries to determine what can one call activities of “Volodko” and “Bilyj” in Wrocław province. Was it a temporary organised group which aimed at transferring ex-members of UPA abroad, or it was, just like C-1 operation, a provocation of MBP to work out the environments of OUN and UPA, or else – was it an ideological or criminal organisation?The material posessed authenticated the statement, that “Volodko” group was not UPA “sensu stricto” or any kind of armed formation. It can be treated as a germ of civil underground structure at most. The least probable seems to be a hypothesisabout the criminal nature of the group, although it accepted some people of very poor reputation. MBP posessed some information about the group, thanks to “Skała” agent among others, nevertheless, according to all possible data, “Volodko” was an agent of local activities aiming to open a transfer channel for exmembers of UPA, ordered by a rival of Bandera fraction of OUN – the Foreign Representation of Ukrainian Main Liberation Committee (ZP UHWR).The subject of the analysis was also determination of the real sequence of events happening because of “Volodko’s” “organisation” existence. It is known, that at least one transfer abroad of the ex-member of UPA was accomplished (BogdanStańko). It was confi rmed that the turning point in the activities of the group were events of October 1949, when “Volodko” was murdered by Jan Kret with pistol shot in the head. Previously unknown threads of Jakub Hirnyj arrest were reconstructed.It was also found out that in connection to “Volodko” case in the period between September 1950 to May 1959 seventeen people got sentences ranging from one year imprisonment to the capital punishment. Authenticity of “Volodko’s” real name, which had “a priori” been accepted to be Włodzimierz Karasiewicz, was questioned. A very probable hypothesis was taken, that “Volodko”, asa “Wujek” was really called Dymitr Tychanicz. The article presents also some information on further lot of main characters connected with the “Volodko’s” case.